STRATEGI KOMUNIKASI SOSIALISASI OLAHRAGA MENEMBAK OLEH PERBAKIN - roring, feky rocky (MediaKom : Jurnal Ilmiah Komunikasi, 2024)
Communication is an interaction between humans, by means of communication humans can relate to one another. The existence of communication can determine the success of a relationship within the scope of a general or formal level, Perbakin is the parent organization for shooting sports that is legal and protected by law. Shooting is the only sport where everything is regulated based on the laws in force in Indonesia, namely that the actors, equipment and implementation of this sport must comply with government regulations. Against the background of the problem of prulaism and complex shooting, researchers try to focus on the construction of a socialization strategy about shooting sports by Perbakin to describe a new paradigm with theoretical, regulatory and empirical approaches to answer what's wrong with shooting. The purpose of this study is to answer the substance of shooting sports in the Indonesian Shooting Association (Perbakin) with a dialectical process of socialization with the stages of externalization, objectivity and internalization in terms of implementing shooting sports in a structured, directed and measurable manner. The theory used by Peter L. Berger and Thomas Luckmann (reality construction; 1966). The research method used in this study uses a qualitative approach with a descriptive study. The method used with efficient data collection used for evaluation is observation of behavior, events and recording of physical characteristics in the repair environment, in this case from the perspective of shooting sports and news seekers about shooting sports. from the results of research on the arrangement of the institutional communication strategy of the Indonesian Shooting Association (Perbakin) organization by competent communicators who understand the material in their fields so that messages through communication media can be conveyed in a measurable and structured manner, this strategy is a logical consequence of fundamental changes related to the existence of repairs and encouragement of adjustments to system and institutional equipment in order to accommodate institutional developments that are increasingly complex and To build shooting sports with integrity requires a conscious and planned effort to create understanding with an active learning process in developing one's potential to have self-control strength, personality, intelligence, noble character, and skills needed by himself, society, nation and state based on Pancasila and the 1945 Constitution of the Republic of Indonesia which are rooted in national values with Indonesian national culture and responsive to the demands of changing times with all educational components that are interrelated in an integrated manner to construct shooting sports.Keywords: Social Communication, Sport, Shooting, Organization, Perbakin